(untitled) (Journal of Comparative & International Higher Education, 2024)
By qualitatively analyzing the case of a higher education unit and reflecting upon its experience of digitalization, the current study attempts to gain insights into how and to what extent digitalization takes place, and what factors facilitate/hinder digitalization efforts in the Turkish context. Data for the present study were collected through individual semi-structured interviews and focus groups. An inductive thematic analysis was employed to identify emerging themes within the data. The findings indicate that there have been both intraorganizational and top-down initiatives towards digitalization, though the latter seems to have failed in addressing intraorganizational needs and priorities. The findings also suggest that the factors that have contributed positively to digitalization are the instructors’ personal interests and availability of many digital tools. However, negative student attitude towards digital tools, problems with online assessments, failure to initiate and maintain a strategic organizational approach towards digitalization and faculty’s reluctance to step outside their comfort zone significantly hinder digitalization.